Heavy Metal Detoxification by Different Bacillus Species Isolated from Solar Salterns - Shameer Syed; Paramageetham Chinthala (Scientifica)
The biosorption mechanism is an alternative for chemical precipitation and ultrafiltration which have been employed to treat heavy metal contamination with a limited success. In the present study, three species of Bacillus which were isolated from solar salterns were screened for their detoxification potential of the heavy metals, lead, chromium, and copper, by biosorption. Biosorption potential of each isolate was determined by Atomic Absorption Spectroscopy (AAS), Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES), and Energy Dispersive Spectroscopy (EDS) as the amount of metal present in the medium after the treatment with the isolates. Bacterial isolates, Bacillus licheniformis NSPA5, Bacillus cereus NSPA8, and Bacillus subtilis NSPA13, showed significant level of lead biosorption with maximum of 87–90% by Bacillus cereus NSPA8. The biosorption of copper and chromium was relatively low in comparison with lead. With the obtained results, we have concluded that the bacterial isolates are potential agents to treat metal contamination in more efficient and ecofriendly manner.